(untitled) (Research, Society and Development, 2022)
Systemic Arterial Hypertension is a multifactorial chronic disease, which, if not treated continuously, considerably increases the risk of cardiovascular events, which can be fatal. For the control of this clinical condition, there is a great diversity of drugs with different mechanisms of action and different adverse effects. Due to the high prevalence of hypertensive patients in dental offices, this study aims to demonstrate the influence of the use of antihypertensive drugs on the development of hyposalivation. Hyposalivation consists of a quantitative decrease in salivary flow, which can be caused by a number of factors, and which leads to the patient’s dry mouth sensation, called xerostomia. This study reviews the most used drug classes for the treatment of systemic arterial hypertension, which have hyposalivation as one of their side effects. Among its various functions, saliva exerts an important control over the oral microbiota. Its absence or the decrease in its normal flow can cause an increase in the prevalence of caries, periodontal disease, opportunistic pathogens and trauma, especially in denture wearers. Finally, methods are proposed to reduce the adverse effects of drugs that cause hyposalivation.